2023
DOI: 10.3389/fimmu.2023.1105664
|View full text |Cite
|
Sign up to set email alerts
|

IL-12α deficiency attenuates pressure overload-induced cardiac inflammation, hypertrophy, dysfunction, and heart failure progression

Abstract: IL-12α plays an important role in modulating inflammatory response, fibroblast proliferation and angiogenesis through modulating macrophage polarization or T cell function, but its effect on cardiorespiratory fitness is not clear. Here, we studied the effect of IL-12α on cardiac inflammation, hypertrophy, dysfunction, and lung remodeling in IL-12α gene knockout (KO) mice in response to chronic systolic pressure overload produced by transverse aortic constriction (TAC). Our results showed that IL-12α KO signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…The finding that depletion of NK1.1 + cells had no significant effect on TAC-induced LV hypertrophy supports the notion that NK1.1 + cells might exert a relatively mild effect on TACinduced LV inflammation and remodeling. The findings that TAC resulted in increased infiltration and activation of pulmonary residential macrophages, Ly6C + monocyte-derived macrophages, dendritic cells, and T cells are consistent with our previous reports (4,5,43). The reduced RV leukocyte infiltration, fibrosis, and hypertrophy in mice after depletion of NK1.1 + cells are likely a collective outcome of reduced pulmonary remodeling and their direct anti-inflammatory effect on RV tissues.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The finding that depletion of NK1.1 + cells had no significant effect on TAC-induced LV hypertrophy supports the notion that NK1.1 + cells might exert a relatively mild effect on TACinduced LV inflammation and remodeling. The findings that TAC resulted in increased infiltration and activation of pulmonary residential macrophages, Ly6C + monocyte-derived macrophages, dendritic cells, and T cells are consistent with our previous reports (4,5,43). The reduced RV leukocyte infiltration, fibrosis, and hypertrophy in mice after depletion of NK1.1 + cells are likely a collective outcome of reduced pulmonary remodeling and their direct anti-inflammatory effect on RV tissues.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, inhibition of inflammation by induction of endogenous regulatory T cells effectively attenuated the transition from LV failure to lung remodeling and RV hypertrophy in mice with existing LV failure ( 5 ). Recently, we further demonstrated that IL12α KO significantly attenuated TAC-induced LV hypertrophy and failure, pulmonary T cell activation, inflammation, fibrosis, and vessel remodeling ( 44 ). Moreover, studies from other groups also demonstrated that LV NK cells, residential macrophages, and monocyte-derived macrophages were significantly increased in mice after TAC ( 31 , 45 ).…”
Section: Discussionmentioning
confidence: 97%